Responding to Patient-Initiated Verbal Sexual Harassment: Outcomes of a Pilot Training for Ophthalmologists - Hock, Lauren E.; Scruggs, Brittni A.; Barlow, Patrick B.; Oetting, Thomas A.; Abràmoff, Michael D.; Shriver, Erin M. (Journal of Academic Ophthalmology, 2020)
Background Sexual harassment of physicians by patients is highly prevalent and rarely reported. Little is known on how to prepare physicians to handle verbal sexual harassment that detracts from their ability to provide care but does not meet the threshold for reporting.Purpose To assess the impact of a sexual harassment workshop and toolkit for ophthalmologists and ophthalmology trainees on responding to patient-initiated verbal sexual harassment.Methods A survey study of ophthalmology faculty, fellows, and residents who participated in workshops on responding to patient-initiated verbal sexual harassment was performed at an academic center. A toolkit of strategies for response was distributed. Volunteer participants completed a retrospective pretest–posttest evaluation at the conclusion of the workshop and follow-up survey 3 weeks after the workshops on whether they experienced harassment and intervened. The pretest–posttest surveys assessed the workshop's effect on ophthalmologists' perceptions of and preparedness to respond to sexual harassment in the moment using a 5-point Likert scale, including bystander intervention. Participants described their responses observing and/or experiencing patient-initiated sexual harassment in the 3 weeks following the workshop and whether they had intervened toward the harassment.Results Ophthalmologists (n = 31) felt significantly more prepared to respond to patient-initiated sexual harassment directed toward themselves or a trainee in the moment after participating in the workshop (4.5 ± 1.63) than before (3.0 ± 1.3) with a mean change of 1.6 (95% confidence interval: 0.98–2.2, p < 0.001). After the workshop, 86.3% of participants felt mostly or completely prepared to respond to comments about their age, gender, marital status, appearance, attractiveness, a specific body part, and sexual or inappropriate jokes. Most participants (83.9%) said that they had not previously received training on techniques for responding to patient-initiated sexual harassment. Two-thirds (66.7%) of participants who experienced (n = 8) or observed (n = 13) harassment (n = 15) following the workshop intervened. All participants who intervened toward patient-initiated harassment behavior after the workshop (n = 10) found the Sexual Harassment Toolkit helpful in addressing harassment in the moment.Conclusion Participation in a brief skills-based workshop significantly improved ophthalmologists' preparedness to respond to verbal sexual harassment by patients.
Keywords: ophthalmology; resident; sexual harassment; toolkit; workshop; patient; training; gender